Determination of static and dynamic fracture initiation toughness and numerical simulation of dynamic 3-point bend experiments of Al6063-T6. (February 2023) - Pandouria, Anoop Kumar; Kumar, Sanjay; Tiwari, Vikrant
Abstract: The objective of this research is to find out the static and dynamic fracture initiation toughness of aluminium alloy Al6063-T6. An in-house modified Hopkinson Pressure Bar (MHPB) along with the digital image correlation (DIC) system has been used for 3-point bend experiments under dynamic loadings. However, conventional UTM has been used for quasi-static experiments. Dynamic experiments have been performed at different projectile velocities of 13.37, 14.23, 15.95, and 20.09 m/s, while quasi-static experiments have been performed at a 1 mm/min displacement rate. Dynamic force is calculated by using strain gauge measurement at two-point on the bar while the crack initiation time is calculated using combined results from strain gauge and digital image correlation. Experimental results found that the value of dynamic fracture initiation toughness (DFIT) is higher as compared to static fracture initiation toughness (SFIT). However, DFIT has continuously increased with increasing loading rates. A numerical simulation of pre notched specimen under 3-point bend dynamic loading has been performed in ABAQUS software using the J-C constitutive and fracture model. Simulation results were compared with the experimental results and found good agreement in both these results.